CONSTRUCTIVISM AND THE PROBLEM OF COMPREHENSION IN MODERN PHILOSOPHY - Ekaterina Vladimirovna Saprykina (Гуманитарные и юридические исследования)
Under the influence of the linguistic turn the paradigm of modern philosophizing is being transformed. The problems of language are coming to the forefront. According to constructivism any knowledge including philosophy is constructed by the subject. Applying this approach to philosophical hermeneutics we can conclude that the comprehension is also constructed in the process of mastering or interpreting a text.